Analysis of Capital Adequacy Ratio, Loan to Deposit Ratio, and Non-Performing Loan on Stock Returns with Interest Rates as a Moderating Variable in the Indonesian Banking Sector - Guterres Riu, Julinha Betty; Hermuningsih, Sri; Hidayat, Riskin (JURNAL MANAJEMEN MOTIVASI, 2025)
This study aims to examine the impact of Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Non-Performing Loans (NPL) on stock returns, as well as the moderating role of interest rates in strengthening or weakening these relationships. The research focuses on banking companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A quantitative and associative approach was employed. The study population consists of 47 banking firms, from which 20 were selected through purposive sampling. Data analysis was conducted using Moderated Regression Analysis (MRA). The findings reveal that CAR and LDR have a positive and significant effect on stock returns, while NPL shows a positive but not significant impact. Furthermore, interest rates do not moderate the relationships between CAR and NPL with stock returns, but they do moderate the relationship between LDR and stock returns.